The Missing Voice: Incorporating the Hindu Community in Developing Inclusive Chaplaincy - Patel, Rushil V. (Journal of pastoral care & counseling, 2022)
This manuscript highlights potential barriers hospitalized Hindu patients and caregivers living in the United States encounter while accessing chaplaincy care. Community-based participatory research is suggested to foster partnerships between chaplains and the Hindu community in developing evidence-based, inclusive models of pastoral care.